Ultrasonography for non-invasive sex identification and reproductive assessment in Nile tilapia (Oreochromis niloticus) - Setthawong, Piyathip; Khemthong, Matepiya; Lertwanakarn, Tuchakorn; Surachetpong, Win (Frontiers in Veterinary Science, 2024)
Sex identification and the selection of monosex male tilapia are crucial for tilapia aquaculture. In this study, we evaluated the application of ultrasonography as an alternative procedure for sex identification and reproductive assessment in Nile tilapia (Oreochromis niloticus). Ultrasonography was performed on 23 fish weighing 232–1,281 g to capture longitudinal and transverse images of the ovaries and testes. Female tilapia were identified by the presence of numerous small egg granules and gray or light gray ovarian tissue and male tilapia by the homogeneous echogenicity and uniform gray tubular appearance of the testes. These distinct echogenic patterns allowed for accurate differentiation between the female and male fish. Ultrasonography achieved a 95% accuracy in sex identification, with minimal stress to the fish during the procedure, compared to manual sex sorting, which demonstrated an accuracy of 87%. Furthermore, the method facilitated the assessment of the reproductive status of the fish, including the maturation stages and fecundity potential. The use of ultrasonography offers significant advantages over traditional methods, such as animal welfare enhancements and improved breeding program efficiency. Our findings support the integration of ultrasonography into aquaculture practices and will promote sustainable and humane fish farming while optimizing reproductive management and productivity.